Impeller material selection method for high-temperature operating temperature section in energy storage compressor
By selecting the appropriate impeller material according to the high-temperature operating temperature section of the energy storage compressor and formulating appropriate heat treatment processes, the mechanical fatigue and thermal fatigue problems of the impeller material under high temperature conditions are solved, and the high-temperature mechanical properties and fatigue properties of the material are improved.
Patent Information
- Application Number
- CN202411474973.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-03-07
AI Technical Summary
The impeller materials of energy storage compressors face mechanical fatigue and thermal fatigue problems during high-temperature operating temperature periods. In the prior art, research on the high-temperature mechanical properties, fatigue limits and thermal fatigue characteristics of the materials are limited.
A method for selecting impeller materials in high-temperature operating temperature sections in energy storage compressors is provided. The appropriate material is selected according to the compressor operating temperature range: FV520B material is selected from the range of 0℃ to 250℃, GH4169 or A286 material is selected from the range of 0℃ to 400℃, and the heat treatment process and chemical composition of each material are formulated.
By selecting the appropriate impeller material and heat treatment process, the yield strength, tensile strength and fatigue properties of the material under high temperature conditions can be effectively improved, the service life of the material can be extended, and early fatigue failure can be avoided.
Smart Images

Figure BDA0005095825530000101 
Figure BDA0005095825530000102 
Figure BDA0005095825530000103
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of compressor impeller materials, and in particular to a method for selecting impeller materials for a medium- and high-temperature operating temperature section of an energy storage compressor. Background Art
[0002] The alternative materials for the impeller of the energy storage compressor are FV520B, Inconel718 (GH4169) and A286. FV520B is a precipitation-strengthened stainless steel, first developed by the British Firth-Vickers Materials Research Laboratory. The steel increases its strength by adding alloying elements to increase the strengthening phase precipitation during the aging process. FV520B has good hardenability and corrosion resistance. Due to its excellent impact resistance and ideal lateral performance on large cross-sections, it has been widely used in compressor impellers, blades, rotors and other parts. A286 is a high-temperature alloy based on Fe-25Ni-15Cr that was discovered early abroad and has mature use experience. It is comprehensively strengthened by adding molybdenum, titanium, aluminum, vanadium and trace elements. It has high yield strength and long-lasting creep strength below 650℃, and has good processing plasticity. It is an iron-based precipitation-strengthened alloy suitable for manufacturing high-temperature load-bearing parts of aircraft engines and gas turbines working below 650℃, such as turbine discs, compressor discs, blades and fasteners. Inconel718 (GH4169) is a Ni-Cr-Fe based deformable high temperature alloy strengthened by precipitation of body-centered tetragonal and face-centered cubic phases. The long-term use temperature range is -253℃~650℃, and the short-term use temperature can reach 800℃. The alloy has high strength below 650℃ and has good fatigue resistance, radiation resistance, oxidation resistance and corrosion resistance. The alloy can meet the application requirements of different rotating parts in aircraft engines and gas turbines.
[0003] At present, the heat treatment process of FV520B and Inconel718 (GH4169) is relatively mature, while the traditional A286 heat treatment process has a general effect on improving the alloy properties.
[0004] Some centrifugal compressor units will start and stop once every 24 hours. During the frequent start-up and shutdown stages, the impeller material will face fatigue problems. This fatigue includes two aspects. One is the mechanical fatigue faced by the material in the operating temperature range, and the other is the temperature cycle change. The fatigue phenomenon caused by the thermal stress cycle is thermal fatigue. In order to avoid early fatigue failure and cause unexpected situations, technicians have a practical and urgent need for the fatigue performance of impeller materials. However, in the prior art, there is limited research on the high-temperature mechanical properties, fatigue limits, fatigue performance change trends, and thermal fatigue characteristics of the above three materials in their respective application temperature ranges. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art or related art.
[0006] To this end, the present invention provides a method for selecting impeller materials for a high temperature operating temperature section of an energy storage compressor, comprising:
[0007] When the compressor operating temperature is between 0℃ and 250℃, the impeller material should be FV520B.
[0008] When the compressor operating temperature is between 0℃ and 400℃, the impeller material should be GH4169 or /
[0009] and A286 material.
[0010] Further, the chemical composition of the FV520B material is, by weight percentage, C: 0.02-0.07%, Si: 0.15-0.7%, Mn: 0.3-1.0%, Cr: 13.0-14.5%, Ni: 5.0-6.0%, Mo: 1.3-1.8%, Cu: 1.3-1.8%, Al: 0-0.03%, and the rest is Fe;
[0011] The chemical composition of the GH4169 material is, by weight percentage, C: 0-0.08%, Si: 0-0.35%, Mn: 0-0.35%, Cr: 17.0-21.0%, Ni: 50.0-55.0%, Mo: 2.8-3.3%, Cu: 0-0.3%, Ti: 0.65-1.15%, Al: 0.2-0.8%, and the rest is Fe;
[0012] The chemical composition of the A286 material is as follows: C: 0-0.08%, Si: 0-1.0%, Mn: 1.0-2.0%, Cr: 13.5-16.0%, Ni: 24.0-27.0%, Mo: 1.0-1.5%, V:
[0013] 0.1~0.5%, Ti: 1.8~2.35%, Al: 0~0.4%, and the rest is Fe.
[0014] Furthermore, the heat treatment process of the FV520B material includes:
[0015] Solution treatment, 1000℃±10℃, keep warm for 1~2h, then air cool;
[0016] After aging treatment, keep at 820℃±10℃ for 1~2h, then oil cool;
[0017] Aging treatment: keep at 440±10℃ for 2~3h, then air cool.
[0018] Furthermore, after heat treatment, the FV520B material has a yield strength of 810-845 MPa at 20°C, a tensile strength of 910-945 MPa at 20°C, a yield strength of 765-805 MPa at 200°C, a tensile strength of 870-910 MPa at 200°C, a yield strength of 695-735 MPa at 350°C, a tensile strength of 775-815 MPa at 350°C, a fatigue strength of 330 MPa-370 MPa at 25°C, a fatigue strength of 300 MPa-340 MPa at 250°C, and a fatigue limit attenuation of 8%-9% at 250°C.
[0019] Furthermore, the heat treatment process of the GH4169 material includes:
[0020] Solution treatment, keep at 950℃±10℃ for 1~3h, then oil cooling;
[0021] Over-aging treatment: keep at 750℃±10℃ for 5~7h, then furnace cool;
[0022] Aging treatment: keep at 680±10℃ for 5~7h, then air cool.
[0023] Furthermore, after the heat treatment process, the GH4169 material has a yield strength of 1090-1125 MPa at 20°C, a tensile strength of 1315-1350 MPa at 20°C, a yield strength of 1060-1100 MPa at 200°C, a tensile strength of 1295-1335 MPa at 200°C, a yield strength of 1015-1055 MPa at 350°C, a tensile strength of 1245-1285 MPa at 350°C, a fatigue strength of 360 MPa-400 MPa at 25°C, a fatigue strength of 330 MPa-370 MPa at 350°C, and a fatigue limit attenuation of 7.5%-8.5% at 350°C.
[0024] Furthermore, the heat treatment process of the A286 material comprises:
[0025] Solution treatment, at 930℃±10℃, keep warm for 2~4h, then oil cool;
[0026] For aging treatment, keep at 650℃±10℃ for 6~8h, then keep at 780±10℃ for 10~13h, and then air cool.
[0027] Furthermore, after heat treatment, the A286 material has a yield strength of 1090-1125 MPa at 20°C, a tensile strength of 1315-1350 MPa at 20°C, a yield strength of 1060-1100 MPa at 200°C, a tensile strength of 1295-1335 MPa at 200°C, a yield strength of 1015-1055 MPa at 350°C, a tensile strength of 1245-1285 MPa at 350°C, an elongation at break of 19%-23% at 350°C, a cross-sectional reduction of 42%-46% at 350°C, a fatigue strength of 290 MPa-325 MPa at 25°C, a fatigue strength of 250 MPa-285 MPa at 350°C, and a fatigue limit attenuation of 11.5%-12.5% at 350°C.
[0028] Furthermore, the yield strength and tensile strength of the FV520B material, the GH4169 material and the A286 material all decrease with increasing temperature; among the three materials, the yield strength and tensile strength of the FV520B material are most affected by temperature, the yield strength and tensile strength of the GH4169 material are second most affected by temperature, and the yield strength and tensile strength of the A286 material are least affected by temperature.
[0029] Further, the ability of the FV520B material to resist thermal fatigue is weaker than that of the A286 material or that of the GH4169 material, and the ability of the A286 material to resist thermal fatigue is equivalent to that of the GH4169 material;
[0030] The FV520B material exhibits thermal fatigue behavior of surface water erosion at 600 cycles, and also exhibits thermal fatigue behavior of surface oxidation; the A286 material exhibits thermal fatigue behavior of surface water erosion at 600 cycles, and no obvious surface oxidation occurs; the GH4169 material exhibits thermal fatigue behavior of surface water erosion at 600 cycles, and no obvious surface oxidation occurs;
[0031] The FV520B material, the A286 material and the GH4169 material all have good ability to resist the influence of temperature rise on fatigue limit at the required operating temperature.
[0032] Compared with the prior art, the present invention has at least the following beneficial effects:
[0033] The method for selecting impeller materials for the medium and high temperature operating temperature section of the energy storage compressor provided by the present invention can select suitable impeller materials according to the specific temperature range of the medium and high temperature operating temperature section of the compressor for use in designing materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] FIG. 1 is a diagram of an exemplary embodiment of the present invention at room temperature ( Figure 1a ) and high temperature ( Figure 1b ) Schematic diagram of standard tensile specimen;
[0035] Figure 2 It is a strength curve diagram of three alloys stretched at different temperatures according to an exemplary embodiment of the present invention;
[0036] Figure 3 A schematic diagram of a thermal fatigue test sample used in an exemplary embodiment of the present invention;
[0037] Figure 4 A schematic diagram of a sample tip notch used in an exemplary embodiment of the present invention;
[0038] Figure 5 are metallographic microstructure micrographs of the surface of the A286 sample at the 0th, 200th, 400th and 600th cycles in an exemplary embodiment of the present invention;
[0039] Figure 6 are metallographic microstructure micrographs of the surface of FV520B steel samples at 0th, 200th, 400th and 600th cycles in an exemplary embodiment of the present invention;
[0040] Figure 7 The metallographic microstructure micrographs of the surface of the Inconel 718 (GH4169) alloy sample at the 0th, 200th, 400th and 600th cycles in an exemplary embodiment of the present invention;
[0041] Figure 8 A schematic diagram of a fatigue specimen used in an exemplary embodiment of the present invention;
[0042] Fig. 9 Fatigue curves of A286 at 25°C (left) and 350°C (right) in an exemplary embodiment of the present invention;
[0043] Fig.10 Fatigue curves of Inconel718 (GH4169) at 25°C (left) and 350°C (right) in an exemplary embodiment of the present invention;
[0044] Fig.11 2 are fatigue curves of FV520B in an exemplary embodiment of the present invention at 25° C. (left) and 250° C. (right). DETAILED DESCRIPTION
[0045] In order to better understand the above technical solution, the technical solution of the present invention is described in detail below through specific embodiments.
[0046] An embodiment of the present invention provides a method for selecting an impeller material for an energy storage compressor in a medium-high temperature operating temperature range, comprising:
[0047] When the compressor operating temperature is between 0℃ and 250℃, the impeller material should be FV520B.
[0048] When the operating temperature of the compressor is between 0℃ and 400℃, the impeller material should be GH4169 material and / or A286 material.
[0049] The embodiment of the present invention provides a method for selecting impeller materials for the medium and high temperature operating temperature section of an energy storage compressor. In order to cope with different operating temperature conditions, a method for selecting impeller materials is proposed. Suitable impeller materials can be selected according to the specific temperature range of the medium and high temperature operating temperature section of the compressor for use in designing materials.
[0050] Specifically, the operating temperature of the compressor is usually between 0 and 250°C, which is called the medium-temperature operating temperature section. The outlet temperature is sometimes even close to a high temperature of 400°C. The operating temperature is between 250°C and 400°C, which is called the high-temperature operating temperature section. If the operating temperature range of the compressor is in the entire temperature section or a certain temperature section within 0°C to 250°C, the impeller material can be FV520B material. If the operating temperature range of the compressor is in the entire temperature section or a certain temperature section within 0°C to 400°C, especially when the operating temperature of the compressor exceeds 250°C, the impeller material can be GH4169 material or / and A286 material.
[0051] The chemical composition of the FV520B material is as follows: C: 0.02-0.07%, Si: 0.15-0.7%, Mn: 0.3-1.0%, Cr: 13.0-14.5%, Ni: 5.0-6.0%, Mo: 1.3-1.8%, Cu: 1.3-1.8%, Al: 0-0.03%, and the rest is Fe; the chemical composition of the GH4169 material is as follows: C: 0-0.08%, Si: 0-0.35%, Mn: 0-0.35%, Cr: 17.0-21.0%, Ni: 50.0-55.0%, Mo: 2.8-3.3%, Cu: 0-0.3%, Ti: 0.65-1.15%, Al: 0.2-0.8%, and the rest is Fe; the A286 material has the following chemical compositions by weight: C: 0-0.08%, Si: 0-1.0%, Mn: 1.0-2.0%, Cr: 13.5-16.0%, Ni: 24.0-27.0%, Mo: 1.0-1.5%, V: 0.1-0.5%, Ti: 1.8-2.35%, Al: 0-0.4%, and the rest is Fe.
[0052] In some embodiments, the heat treatment process of the FV520B material includes:
[0053] Solution treatment, 1000℃±10℃, keep warm for 1~2h, then air cool;
[0054] After aging treatment, keep at 820℃±10℃ for 1~2h, then oil cool;
[0055] Aging treatment: keep at 440±10℃ for 2-3h, then air cool;
[0056] After the above-mentioned FV520B material is heat treated, the yield strength of the FV520B material at 20°C is 810-845MPa, the tensile strength at 20°C is 910-945MPa, the yield strength at 200°C is 765-805MPa, the tensile strength at 200°C is 870-910MPa, and the yield strength at 350°C is
[0057] 695~735MPa, tensile strength at 350℃ is 775~815MPa, fatigue strength at 25℃ is 330MPa~370MPa, fatigue strength at 250℃ is 300MPa~340MPa, fatigue limit attenuation at 250℃ is 8%~9%.
[0058] In some embodiments, the heat treatment process of the GH4169 material comprises:
[0059] Solution treatment, keep at 950℃±10℃ for 1~3h, then oil cooling;
[0060] Over-aging treatment: keep at 750℃±10℃ for 5~7h, then furnace cool;
[0061] Aging treatment: keep at 680±10℃ for 5~7h, then air cool.
[0062] After the above-mentioned heat treatment process, the yield strength of GH4169 material at 20°C is 1090~1125MPa, the tensile strength at 20°C is 1315~1350MPa, the yield strength at 200°C is 1060~1100MPa, the tensile strength at 200°C is 1295~1335MPa, the yield strength at 350°C is 1015~1055MPa, the tensile strength at 350°C is 1245~1285MPa, the fatigue strength at 25°C is 360MPa~400MPa, the fatigue strength at 350°C is 330MPa~370MPa, and the fatigue strength at 350°C is 350MPa~360MPa.
[0063] The lower fatigue limit decays by 7.5% to 8.5%.
[0064] In some embodiments, the heat treatment process of the A286 material includes:
[0065] Solution treatment, at 930℃±10℃, keep warm for 2~4h, then oil cool;
[0066] For aging treatment, keep at 650℃±10℃ for 6~8h, then keep at 780±10℃ for 10~13h, and then air cool.
[0067] After the above-mentioned A286 material is heat treated, the yield strength of the A286 material at 20°C is 1090-1125MPa, the tensile strength at 20°C is 1315-1350MPa, the yield strength at 200°C is 1060-1100MPa, the tensile strength at 200°C is 1295-1335MPa, the yield strength at 350°C is 1015-1055MPa, the tensile strength at 350°C is 1245-1285MPa, the elongation at 350°C is 19%-23%, the cross-sectional shrinkage at 350°C is 42%-46%, the fatigue strength at 25°C is 290MPa-325MPa, the fatigue strength at 350°C is 250MPa-285MPa, and the fatigue limit attenuation at 350°C is 11.5%-12.5%.
[0068] We explored the temperature-dependent strength changes of FV520B, GH4169 and A286 materials, and the conclusions are as follows: the yield strength and tensile strength of FV520B, GH4169 and A286 materials all decrease with increasing temperature; among the three materials, the yield strength and tensile strength of FV520B are most affected by temperature, the yield strength and tensile strength of GH4169 are second most affected by temperature, and the yield strength and tensile strength of A286 are least affected by temperature.
[0069] We explored the fatigue performance of FV520B, GH4169 and A286 materials and concluded as follows:
[0070] The ability of FV520B material to resist thermal fatigue is weaker than that of A286 material or GH4169 material. The ability of A286 material to resist thermal fatigue is equivalent to that of GH4169 material. Specifically, FV520B material exhibits thermal fatigue behavior of surface water erosion under 600 cycles, and also has thermal fatigue behavior of surface oxidation; A286 material exhibits thermal fatigue behavior of surface water erosion under 600 cycles, and no obvious surface oxidation occurs; GH4169 material exhibits thermal fatigue behavior of surface water erosion under 600 cycles, and no obvious surface oxidation occurs. As for the fatigue limit situation:
[0071] FV520B material, A286 material and GH4169 material all have good ability to resist the influence of temperature rise on fatigue limit at the required operating temperature (when the compressor operating temperature is between 0℃ and 250℃, the impeller material is FV520B material; when the compressor operating temperature is between 0℃ and 400℃, the impeller material is GH4169 material or / and A286 material).
[0072] The following is an in-depth discussion of the high-temperature mechanical properties, fatigue limits, fatigue performance change trends, and thermal fatigue characteristics of FV520B, A286, and GH4169 materials in their respective medium and high temperature application temperature ranges, and conclusions are drawn for use in design and material selection.
[0073] At present, the heat treatment process we have mastered for FV520B material and Inconel718 (GH4169) material fully meets the requirements of impeller speed. Therefore, the present invention no longer specifically optimizes and improves the heat treatment process of the above two materials. The heat treatment process performed by the above materials in this project and the corresponding yield strength are shown in Table 1.
[0074] Table 1 Heat treatment process of FV520B steel and Inconel718 (GH4169)
[0075] Material Heat treatment process Yield strength / MPa FV520B 1000℃2hAC+820℃1.5h OC+440℃2h AC 828 Inconel718 950℃×2hOC+750℃×6h, furnace cooling to 680℃×6hAC 1106
[0076] The strength of A286 forgings under standard heat treatment conditions is low, so the present invention optimizes the heat treatment process of high-temperature alloy A286, aiming to improve its strength index, give full play to the potential of comprehensive mechanical properties and high temperature resistance of the material, and meet the strength value required by the impeller when working. First, the heat treatment process of A286 was explored, and the heat treatment scheme and the corresponding mechanical properties are shown in Table 2, where No. 7 is the heat treatment process used for A286 material in the prior art.
[0077] Table 2 Heat treatment process of A286
[0078] serial number Heat treatment process Rs(MPa) Rm(MPa) 1 930℃×3hOC+700℃×6hAC 587 884 2 930℃×3hOC+700℃×12hAC 679 910 3 930℃×3hOC+720℃×6hAC 628 919 4 930℃×3hOC+720℃×12hAC 692 928 5 930℃×3hOC+650℃×7h+780℃×12hAC 710 966 6 930℃×3hOC+650℃×7h+780℃×16hAC 615 915 7 950℃×3hOC+750℃×6hAC 600 903
[0079] The standard heat treatment process of the alloy is derived from the relevant provisions in the aviation industry implementation standard HB / Z 140, in which the heat treatment system for forged bars and forgings is 990℃±10℃×(1~2)h / OC+(700~720)℃×16h / AC. According to the standard process, heat treatment schemes No. 1 to No. 4 were formulated. As shown in Table 2, the experimental results show that the mechanical properties are best under the aging condition of 720℃. Increasing or decreasing the aging temperature and shortening the aging time will affect the heat treatment effect. It is known from the data that the dispersion strengthening phase Ni3(Ti, Al) type γ' phase of the A286 alloy will increase in quantity after long-term aging at 550~650℃, which will help improve the mechanical properties. Therefore, two heat treatment schemes No. 5 and No. 6 in Table 3 were formulated, and the intermediate aging process at 650℃ was added. The results show that the mechanical properties are best when the temperature is raised to 780℃ and then kept at 12h for aging after aging at 650℃ for 7h. The heat treatment system corresponding to No. 5 is also defined as the implementation process of the A286 material of the present invention.
[0080] The mechanical properties of metal materials in high temperature environments will decay compared to those in normal temperature environments, that is, the material's ability to resist deformation due to external forces will decrease. This is because the dislocation slip speed increases as the temperature rises. In order to ensure the reliable operation of the energy storage compressor, the selection of its core component, the impeller, must fully consider the impact of temperature on mechanical properties. Therefore, it is necessary to test and analyze the high-temperature tensile properties of the impeller candidate materials.
[0081] The three materials, FV520B, A286 and Inconel718, were stretched at different temperatures to obtain their stress-strain curves, and then the yield strength and tensile strength of the materials were calculated. The yield strength and tensile strength at a specific temperature were obtained, and the effect of temperature on their performance was analyzed.
[0082] The room temperature tensile test was designed in accordance with GB / T 228 Tensile test method for metal materials.
[0083] The high temperature tensile test is designed in accordance with GB / T 228.2-2015 High temperature test methods for metal materials. The high temperature test temperature range is 150-500℃.
[0084] First, number the three materials, mark the A286 high-temperature alloy material as sample D1#; mark the Inconel718 nickel-chromium-iron alloy material as sample D2#; and mark the FV520B stainless steel material as sample D5# to avoid material confusion.
[0085] Sample processing: The three alloy materials were processed into standard tensile specimens, and the specific dimensions of the specimens are shown in Figure 1. The tensile test was carried out using specimens of this size.
[0086] The tensile test equipment is a CMT5205 / 5305 series electronic universal testing machine, which fully meets the requirements of GB / T228-2002 "Room Temperature Tensile Test Method for Metallic Materials".
[0087] The tensile test results are as follows:
[0088] Table 3 FV520B tensile test results
[0089]
[0090] FV520B tensile curve Figure 2 The yield strength of FV520B material at 20℃ is 827.68MPa, and the tensile strength is 928.00MPa; with the increase of temperature, the yield strength and tensile strength decrease steadily, and the final yield strength at the set maximum temperature of 350℃ is 714.25MPa, and the tensile strength is 795.95MPa. After the temperature is raised from 20℃ to 350℃, the decrease rates of yield strength and tensile strength are 13.7% and 14.2% respectively.
[0091] Table 4 A286 tensile test results
[0092]
[0093] A286 tensile curve Figure 2 The yield strength of A286 material at 20℃ is 663.27MPa, and the tensile strength is 1020.00MPa; the yield strength at 350℃ is 638.34MPa, and the tensile strength is 952.62MPa. As the temperature rises, the strength of A286 material decreases accordingly, but compared with FV520B, its decrease is smaller. After the temperature rises from 20℃ to 350℃, the decrease rates of its yield strength and tensile strength are 3.8% and 6.7% respectively.
[0094] Table 5 Inconel718 tensile test results
[0095]
[0096] Inconel718 tensile curve Figure 2 , the yield strength of Inconel718 material at 20℃ is 1105.71MPa, and the tensile strength is 1333.47MPa; the yield strength at 350℃ is 1034.87MPa, and the tensile strength is 1268.11MPa. As the temperature rises, the strength of Inconel718 material decreases accordingly. After the temperature rises from 20℃ to 350℃, the decrease rates of its yield strength and tensile strength are 6.4% and 4.9% respectively.
[0097] Tensile test conclusion: The yield strength and tensile strength of the three materials decrease with increasing temperature, but the degree of temperature influence on the three materials is different. FV520B is greatly affected by temperature, and its yield strength and tensile strength are significantly reduced, while Inconel718 and A286 are less affected by temperature. Under the same temperature change conditions, the strength reduction of A286 is slightly greater than that of Inconel718. Considering the factors of strength attenuation rate and economic benefits, when the temperature and stress are low, it is recommended to use FV520B material; when the temperature and stress are high, it is recommended to use A286 material first.
[0098] The purpose of the fatigue test is to conduct cyclic thermal tests on three materials, FV520B, A286 and Inconel718, with heating and cooling, and then analyze the evolution of the thermal fatigue behavior of the three materials with the thermal fatigue cycle.
[0099] (I) Thermal fatigue test plan: The test is carried out in accordance with GB / T 15824-2008 "Thermal fatigue test method for hot working die steel". The sample drawing is as follows: Figure 3 shown.
[0100] The V-shaped notch on the side of the sample is used to determine the risk of tip cracking. The notch size is as follows: Figure 4 As shown. The test was conducted on a self-designed thermal fatigue testing machine. The test principle was based on the Swedish Uddeholm thermal fatigue test method. The sample was heated to the upper limit temperature (Tmax) by medium-high frequency induction rapid heating and then cooled to the lower limit temperature (Tmin) by water spray rapid cooling. The sample generates thermal stress due to internal constraints. After a certain number of cycles, it is determined whether the thermal fatigue damage on the sample surface and the risk of cracking at the tip of the V-notch exist.
[0101] Thermal fatigue test results:
[0102] The evolution of thermal fatigue behavior of A286 steel with cycles is shown in Figure 5 , Figure 5 The metallographic state of the A286 sample surface at the 0th, 200th, 400th and 600th cycles under 25 times. It can be found that with the increase of the test cycle, the water erosion phenomenon on the sample surface is significantly aggravated.
[0103] The evolution of thermal fatigue behavior of FV520B stainless steel with cycles is shown in Figure 6 , Figure 6 The metallographic state of the FV520B sample surface at the 0th, 200th, 400th and 600th cycles under 25 times. It can be found that with the increase of the test cycle, the water erosion phenomenon on the sample surface is significantly aggravated.
[0104] The evolution of thermal fatigue behavior of Inconel718 alloy with cycles is shown in Figure 7 , Figure 7The metallographic state of the Inconel 718 alloy sample surface at 0, 200, 400 and 600 cycles under 25 times. It can be found that with the increase of the test cycle, the water erosion phenomenon on the sample surface is significantly aggravated, and slight surface oxidation can be seen at the water erosion. The sample as a whole does not show obvious surface oxidation, which is similar to the A286 steel test sample.
[0105] The test samples 1 (A286 steel) and 3 (Inconel 718 alloy) were calibrated at temperatures of Tmax = 370°C ± 20°C and Tmin = 20°C ± 20°C. The test samples 2 (FV520B steel) were calibrated at temperatures of Tmax = 270°C ± 20°C and Tmin = 20°C ± 20°C. Each 90s test cycle (heating time of 60s and cooling time of 30s) was conducted for a total of 600 cycles. The test conclusions are as follows:
[0106] Under 600 cycles, both test sample 1 (A286 steel) and test sample 3 (Inconel 718 alloy) mainly exhibit thermal fatigue behavior of water erosion and have similar surface oxidation resistance.
[0107] Compared with test sample 1 (A286 steel) and test sample 3 (Inconel 718 alloy), under 600 cycles, test sample 2 (FV520B steel) not only exhibits thermal fatigue behavior of surface water erosion, but also has severe thermal fatigue behavior of surface oxidation.
[0108] Test sample 1 (A286 steel), test sample 2 (FV520B steel) and test sample 3 (Inconel 718 alloy) did not show surface cracks after 600 cycles.
[0109] In general, the ability of test sample 2 (FV520B steel) to resist thermal fatigue is weaker than that of sample 1 and sample 3.
[0110] (II) Fatigue limit test
[0111] The following fatigue tests are carried out on three materials, FV520B, A286 and Inconel718, at different temperatures to obtain their fatigue limits and analyze the differences in fatigue properties of the materials at different temperatures.
[0112] The test was carried out in accordance with GB / T 3075 Axial Stress Control Method for Fatigue Test of Metal Materials.
[0113] First, number the three materials, mark the A286 high-temperature alloy material as sample D1#; mark the Inconel718 nickel-chromium-iron alloy material as sample D2#; and mark the FV520B stainless steel material as sample D5# to avoid material confusion.
[0114] Sample processing: The three alloy materials are processed into standard tensile specimens. The specific dimensions of the specimens are as follows: Figure 8 The tensile test was carried out using a specimen of this size.
[0115] The fatigue test equipment is GPS200 high frequency fatigue testing machine, with a maximum static load of 200KN, a maximum dynamic load of 100KN, and a frequency of 80-250HZ.
[0116] Clean the surface of the sample and set the test force according to the principle of the lifting method. The test force ranges from 4KN to 11KN. The experimental group under each load is recorded in the form of DX-XXX-XX. For example, D2-350-7-1 represents the first test of the Inconel718 material represented by D2 under a load of 7KN and a temperature of 350°C. Since the center diameter of the sample is 5mm, the corresponding stress magnitude can be calculated according to the set load, and the number of cycles under this stress can be recorded, and then the SN curve and fatigue limit of the material can be obtained. Taking 6.5KN as an example, set the load to 6.5KN, the average load to 0KN, the alternating load to 6.5KN, the stress ratio to -1, the vibration frequency to 139.5HZ, and set the upper limit of the number of cycles to 10 7 When the experiment runs to the upper limit of cycles or runs to the fracture limit, the experiment machine will have frequency protection or load protection, and the test will automatically stop. At this time, the cycle number under this load is recorded, that is, the cycle life of the material under this working condition. After a series of fatigue tests, we selected some key load points and displayed the fracture conditions of the test specimens after the test. When the load is low, the specimen can be cycled to 10 7 As the load increases, the number of cycles of the specimen will decrease and fracture will occur.
[0117] The fatigue test data points of the sample recorded after the test are counted, and the stress amplitude is used as the ordinate of the SN curve, and the abscissa is the number of test cycles. The relevant mathematical formula of the SN curve is used for fitting, and MATLAB is used for data processing and curve fitting to obtain the final SN curve. From the SN curve, we can get the fatigue limit of the material.
[0118] Fatigue test results:
[0119] A286 fatigue curve Fig. 9 As shown in the figure, at 25°C, when the stress of A286 material was 318.31Mpa, the fatigue cycles of the first group of tests reached 4.02x10 6 Week, the second group of experiments reached 1.00x10 7To ensure the accuracy of the test under this stress, a test was conducted at a lower stress of 305.58Mpa. The fatigue cycles under this stress reached 1.00x10 7 Therefore, it can be considered that the fatigue limit of A286 at 25°C is 304.72Mpa. At 350°C, when the stress of A286 material is 280.11Mpa, the fatigue cycles of the first group of tests reached 2.85x10 6 Week, the second group of experiments reached 1.00x10 7 To ensure the accuracy of the test under this stress, a test under a lower stress of 267.38Mpa was conducted, and the fatigue cycles under this stress reached 1.00x10 7 Therefore, it can be considered that the fatigue limit of A286 at 350°C is 267.36Mpa. According to the above measured data, compared with room temperature, the fatigue strength decay rate of A286 at 350°C is 12.3%.
[0120] Inconel718 fatigue curve Fig.10 As shown in the figure, at 25°C, when the stress of Inconel718 material is 394.7Mpa, the fatigue cycles of the first group of tests reached 6.35x10 6 Week, the second group of experiments reached 1.00x10 7 To ensure the accuracy of the test under this stress, a test under a lower stress of 381.97Mpa was conducted, and the fatigue cycles under this stress reached 1.00x10 7 Therefore, it can be considered that the fatigue limit of Inconel718 at 25°C is 379.55Mpa. At 350°C, when the stress of Inconel718 material is 356.51Mpa, the fatigue cycles of the first group of tests reached 6.68x10 6 Week, the second group of experiments reached 1.00x10 7 To ensure the accuracy of the test under this stress, a test under a lower stress of 343.78Mpa was conducted, and the fatigue cycles under this stress reached 1.00x10 7 Therefore, it can be considered that the fatigue limit of Inconel718 at 350°C is 349.84Mpa. According to the above measured data, compared with room temperature, the fatigue strength decay rate of Inconel718 at 350°C is 7.8%.
[0121] FV520B fatigue curve Fig.11 As shown in the figure, at 25°C, when the stress of FV520B material is 356.53Mpa, the fatigue cycles of the first group of tests reached 8.00x10 6Week, the second group of experiments reached 1.00x10 7 To ensure the accuracy of the test under this stress, a test under a lower stress of 343.68Mpa was conducted, and the fatigue cycles under this stress reached 1.00x10 7 Therefore, it can be considered that the fatigue limit of FV520B at 25°C is 347.8Mpa. At 250°C, when the stress of FV520B material is 331.04Mpa, the fatigue cycles of the first group of tests reached 3.50x10 6 Week, the second group of experiments reached 1.00x10 7 To ensure the accuracy of the test under this stress, a test under a lower stress of 318.31Mpa was conducted, and the fatigue cycles under this stress reached 1.00x10 7 Therefore, it can be considered that the fatigue limit of FV520B at 250°C is 318.78Mpa. According to the above measured data, compared with room temperature, the fatigue strength attenuation rate of FV520B at a higher temperature of 250°C is 8.3%.
[0122] in conclusion:
[0123] The fatigue strength of A286 material at 25°C is 304.72MPa, and the fatigue strength at 350°C is 267.36MPa; the fatigue strength of FV520B material at 25°C is 347.8MPa, and the fatigue strength at 250°C is 318.78MPa; the fatigue strength of Inconel718 material at 25°C is 379.55MPa, and the fatigue strength at 350°C is 349.84MPa.
[0124] The fatigue strength attenuation rates of A286, Inconel718 and FV520B are 10%, 7.9% and 6.4% respectively, of which the test temperature of A286 and Inconel718 is 350℃, and the test temperature of FV520B steel is 250℃. The attenuation of the three materials is not large, that is, they have good ability to resist the adverse effect of temperature on fatigue limit at their respective working temperatures.
[0125] In summary, the results of the present invention can help technicians select materials for use, and using this data to select materials is beneficial to the long-term safe operation of the impeller.
[0126] It is easy for those skilled in the art to understand that, under the premise of no conflict, the above-mentioned advantageous methods can be freely combined and superimposed. The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application. The above are only preferred implementation methods of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present application, and these improvements and variations should also be regarded as the protection scope of the present application.
Claims
1. A method for selecting impeller materials for a high temperature operating temperature range of an energy storage compressor, characterized in that: include: When the compressor operating temperature is between 0℃ and 250℃, the impeller material should be FV520B. When the operating temperature of the compressor is between 0℃ and 400℃, the impeller material should be GH4169 material and / or A286 material.
2. The method for selecting impeller materials for the high temperature operating temperature section of the energy storage compressor according to claim 1, characterized in that: The chemical composition of the FV520B material is as follows: C: 0.02-0.07%, Si: 0.15-0.7%, Mn: 0.3-1.0%, Cr: 13.0-14.5%, Ni: 5.0-6.0%, Mo: 1.3-1.8%, Cu: 1.3-1.8%, Al: 0-0.03%, the rest is Fe; The chemical composition of the GH4169 material is as follows: C: 0-0.08%, Si: 0-0.35%, Mn: 0-0.35%, Cr: 17.0-21.0%, Ni: 50.0-55.0%, Mo: 2.8-3.3%, Cu: 0-0.3%, Ti: 0.65-1.15%, Al: 0.2-0.8%, and the rest is Fe; The chemical composition of the A286 material is as follows: C: 0-0.08%, Si: 0-1.0%, Mn: 1.0~2.0%, Cr: 13.5~16.0%, Ni: 24.0~27.0%, Mo: 1.0~1.5%, V: 0.1~0.5%, Ti: 1.8~2.35%, Al: 0~0.4%, and the rest is Fe.
3. The method for selecting impeller materials for the high temperature operating temperature section of the energy storage compressor according to claim 1, characterized in that: The heat treatment process of the FV520B material includes: Solution treatment, 1000℃±10℃, keep warm for 1~2h, then air cool; After aging treatment, keep at 820℃±10℃ for 1~2h, then oil cool; Aging treatment: keep at 440±10℃ for 2~3h, then air cool.
4. The method for selecting impeller materials for the high temperature operating temperature section of the energy storage compressor according to claim 3, characterized in that: After heat treatment, the FV520B material has a yield strength of 810-845 MPa at 20°C, a tensile strength of 910-945 MPa at 20°C, a yield strength of 765-805 MPa at 200°C, a tensile strength of 870-910 MPa at 200°C, a yield strength of 695-735 MPa at 350°C, a tensile strength of 775-815 MPa at 350°C, a fatigue strength of 330 MPa-370 MPa at 25°C, a fatigue strength of 300 MPa-340 MPa at 250°C, and a fatigue limit attenuation of 8%-9% at 250°C.
5. The method for selecting impeller materials for the high temperature operating temperature section of the energy storage compressor according to claim 1, characterized in that: The heat treatment process of the GH4169 material includes: Solution treatment, keep at 950℃±10℃ for 1~3h, then oil cooling; Over-aging treatment: keep at 750℃±10℃ for 5~7h, then furnace cool; Aging treatment: keep at 680±10℃ for 5~7h, then air cool.
6. The method for selecting impeller materials for the medium and high temperature operating temperature section of the energy storage compressor according to claim 5, characterized in that: After the heat treatment process, the GH4169 material has a yield strength of 1090-1125 MPa at 20°C, a tensile strength of 1315-1350 MPa at 20°C, a yield strength of 1060-1100 MPa at 200°C, a tensile strength of 1295-1335 MPa at 200°C, a yield strength of 1015-1055 MPa at 350°C, a tensile strength of 1245-1285 MPa at 350°C, a fatigue strength of 360 MPa-400 MPa at 25°C, a fatigue strength of 330 MPa-370 MPa at 350°C, and a fatigue limit attenuation of 7.5%-8.5% at 350°C.
7. The method for selecting impeller materials for the medium and high temperature operating temperature section of the energy storage compressor according to claim 1, characterized in that: The heat treatment process of the A286 material includes: Solution treatment, at 930℃±10℃, keep warm for 2~4h, then oil cool; For aging treatment, keep at 650℃±10℃ for 6~8h, then keep at 780±10℃ for 10~13h, and then air cool.
8. The method for selecting impeller materials for the high temperature operating temperature range of the energy storage compressor according to claim 7, characterized in that: After heat treatment, the A286 material has a yield strength of 1090-1125 MPa at 20°C, a tensile strength of 1315-1350 MPa at 20°C, a yield strength of 1060-1100 MPa at 200°C, a tensile strength of 1295-1335 MPa at 200°C, a yield strength of 1015-1055 MPa at 350°C, a tensile strength of 1245-1285 MPa at 350°C, an elongation after fracture of 19%-23% at 350°C, a cross-sectional shrinkage of 42%-46% at 350°C, a fatigue strength of 290 MPa-325 MPa at 25°C, a fatigue strength of 250 MPa-285 MPa at 350°C, and a fatigue limit attenuation of 11.5%-12.5% at 350°C.
9. The method for selecting impeller materials for the high temperature operating temperature range of the energy storage compressor according to any one of claims 1 to 8, characterized in that: The yield strength and tensile strength of the FV520B material, the GH4169 material and the A286 material all decrease with increasing temperature; among the three materials, the yield strength and tensile strength of the FV520B material are most affected by temperature, the yield strength and tensile strength of the GH4169 material are second most affected by temperature, and the yield strength and tensile strength of the A286 material are least affected by temperature.
10. The method for selecting impeller materials for the medium and high temperature operating temperature range of the energy storage compressor according to any one of claims 1 to 8, characterized in that: The ability of the FV520B material to resist thermal fatigue is weaker than that of the A286 material or that of the GH4169 material, and the ability of the A286 material to resist thermal fatigue is equivalent to that of the GH4169 material; The FV520B material exhibits thermal fatigue behavior of surface water erosion and surface oxidation thermal fatigue under 600 cycles; The A286 material exhibits thermal fatigue behavior of surface water erosion under 600 cycles, and no obvious surface oxidation occurs; the GH4169 material exhibits thermal fatigue behavior of surface water erosion under 600 cycles, and no obvious surface oxidation occurs; The FV520B material, the A286 material and the GH4169 material all have good ability to resist the influence of temperature rise on fatigue limit at the required operating temperature.